Sustainability of Performance of Teacher-awardees’ Instructional Competence and Teaching Effectiveness - Aquino, Paulo Martin M. (ASEAN Journal of Educational Research and Technology, 2024)
The study focused on finding good strategies to be applicable and timely in the new normal condition. We investigated whether the teacher-awardees sustained their performances in instructional competence and teaching effectiveness. This study is beneficial since its focus is on determining the extent of the level of sustainability of performance in instructional competence and teaching effectiveness which need to be taken into consideration by utilizing the analytical tool provided by the researcher and by providing seminars and training targeting how to give importance on their performances in instructional competence and teaching effectiveness which will be beneficial to their teaching profession and well-being.